Sistem Pendeteksi Sampah Secara Realtime Menggunakan Metode YOLO - Priana, Kadek Adi; Eka Karyawati, Anak Agung Istri Ngurah (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
At present, people’s daily garbage is increasing day by day. How to intelligently classify garbage can save manpower and improve work efficiency. In this paper, a garbage classification model based on. First, according to the common daily garbage category, twelve typical kinds of garbage were selected, data cleaned, labeled, and constructed a garbage dataset. Second, the YOLO was built and trained on our datasets. The experimental results show that YOLO can accurately identify the garbage’s types and find out the location of garbage.